The Significance of Ramana Maharshi's Self-Enquiry for Meditation - DAYEONG PARK; SURESH L. BARNAWAL (Dr. Chinmay Pandya, 2017)
Seeking happiness has become a crucial part of human beings due to a consistent rise in anxiety and stress over the passing years. As a result, the importance of Indian meditation practices has risen worldwide. Especially, Ramana Maharshi's Self-enquiry is one of the significant meditation practices found in India. The purpose of this paper is to show that Mokṣa (liberation), where one is free from suffering, can be attained by the practice of Self-enquiry, which is simple but powerful because it immediately pierces to the core, the Self. Ramana is the ancient traditional master in India, and he is also known for using silence in the instruction of his disciples. The essence of Self-enquiry is that it is not to realize something anew but to abide as the Self, in the here and now with aware affirmation "I am already Thou." Ramana's life, the experience of his great awakening, the Self, 'I'-thought, the body, the theoretical aspect of Self-enquiry as meditation by Ramana and the practical aspect of Self-enquiry as meditation by Prof. Kim Kyeungmin are presented to illustrate the significance of this method. It is pointed out that Maharshi's Self-enquiry is more valuable and productive than other meditation techniques.